Experimental and computational investigation into oil shedding from an aeroengine ball bearing - Hee, Jee Loong (2020)
Aero-engines contain ball bearings that support the shafts and react to the loads. During the investigation of improvements and the pursuit for higher bypass ratio, propulsion and thermal efficiency, regimes are explored where an aero-engine’s core is subjected to higher mechanical and thermal loadings as it is required to operate at a higher temperature, pressure and speed. There is thus a need for continual development in aero-engine oil systems in order to meet the demands for optimised cooling and lubrication ie good cooling performance without increasing engine weight. Using computational fluid dynamics (CFD) to model aeroengine transmissions elements and systems is an attractive research approach but a pre-requisite for an accurate simulation lies within the ‘exactness’ of the boundary conditions. The research presented in this thesis is dedicated to understanding the oil shedding process of an aero-engine ball bearing operating at moderate speeds and to acquire the boundary conditions for CFD simulations. This thesis further presents a computational investigation that develops bearing chamber modelling techniques.